Maximum Standard Uptake Value as a Clinical Biomarker for Detecting Loss of SMAD4 Expression and Early Systemic Tumor Recurrence in Resected Left-Sided Pancreatic Cancer - Kang, Chang Moo (Medicine (Baltimore), 2016)
This study investigated the oncologic impact of loss of SMAD4 expression in resected left-sided pancreatic cancer and its correlation with tumor metabolism. From 2005 to 2011, the medical records of patients who underwent radical distal pancreatectomy for resectable pancreatic cancer were retrospectively reviewed. Formalin-fixed, paraffin embedded tissue from 32 patients was investigated. Clinicopathological characteristics, immunostaining of SMAD4, and positron emission tomography-based parameters were analyzed in relation to oncologic outcomes. Thirteen patients were women and 19 were men, with a mean age of 63 ± 9.4 years. Mean resected tumor size was 3.3 ± 1.5 cm. Ten patients (31.3%) showed loss of SMAD4 expression. No significant clinicopathological differences were noted according to SMAD4 expression (P > 0.05); however, patients with loss of SMAD4 showed significantly poorer disease-free survival (mean 57.4 months vs mean 17.6 months, P = 0.006). As a cut-off value, a SUV(max) of 4.5 was found to be predictive of loss of SMAD4 with a sensitivity of 75% and a specificity of 84.6%. In logistic regression analysis, SUV(max)>4.5 was found to infer a 16-fold higher risk for loss of SMAD4 in resected left-sided pancreatic cancers (Exp[β] = 16.5, P = 0.012, 95% confidence interval: 1.832–148.606). Loss of SMAD4 is associated with poor oncologic outcomes. SUV(max) can predict loss of SMAD4 in resected left-sided pancreatic cancer. SUV(max) may be a clinical biomarker for detecting loss of SMAD4 expression and predicting early systemic metastasis.